Conceptual Ideal Supervision of the Corruption Eradication Commission in Eradicating Corruption Crimes - Atty Novyanty (Universitas Airlangga, 2022)
One law enforcement agency that has the authority to carry out full supervision and investigation of corruption cases is the Corruption Eradication Commission. Article 50, paragraph (1) is problematic where the arrangement is incomplete and seems unclear. There is also a problem in the implementation of article 50, paragraph (3) concerning the phrase ‘The police or the prosecutor's office is no longer authorised to conduct a full investigation’. Article 50, paragraph (1) of Law No 30/2002 on the Commission for the Eradication of Corruption Crime (‘KPK Law’) provides that ‘in the event that a corruption crime occurs and the Corruption Eradication Commission has not conducted a full investigation, while the case has been fully investigated by the police or the prosecutor's office’. Article 10, paragraph (2) of Law No 19/2019 on the Second Amendment to Law No 30/2002 on the Commission for the Eradication of Corruption Crime (‘Law No 19/2019 on the Second Amendment to the KPK Law’) causes a problem because the provisions on the implementation of supervision duties should be regulated in the form of government regulations by referring to an adherence to the principle.